THE STRATEGY OF THE PRINCIPAL IN IMPROVING THE QUALITY OF ISLAMIC RELIGIOUS EDUCATION IN SCHOOL - Fia Novita; Raihan Tasnim (Proceeding International Seminar of Islamic Studies, 2022)
The objectives of this study include (1) to determine the principal's strategy in improving the quality of Islamic education in schools; (2) Analyzing the strategies given by the Principal in improving the quality of Islamic Religious Education; (3) Knowing whether the strategy given by the principal works in improving the quality of Islamic Religious Education in schools. The approach taken in this research is a descriptive qualitative method in the form of interviews with the principal. The research was in the form of interviews with school principals and was conducted in one school. In this case, there are several strategies that have been made by the Principal, there are strategies that work and there are also strategies that have not worked, because they are caused by several factors. These factors are being addressed by school principals in order to improve the quality of Islamic religious education in schools. And this strategy is not only applied to students but also to teachers and all school stakeholders. Based on the results of the study, it can be concluded that the principal's strategy will work well, if all schools participate in implementing strategies to improve the quality of Islamic Religious Education in schools.Keywords: Strategy, Principal, Quality, Islamic Religious Education